Outcomes and associated factors of cervical human papillomavirus infection among 608 women in Shenzhen, China, 2018–2023 - Zhenghan Lv; Xuesen He; Zhiju Li; Yue Yuan; Xinyi Zhou; Changqing Tu; Yinqi Yang; Yanshan Huang; Lili Yin; Huihui Chen; Yanling Tao; Yanling Tao (Frontiers in Public Health)
ObjectiveThis study aimed to uncover the patterns of Human papillomavirus (HPV) infection outcomes in women and assess the risk factors that may affect these outcomes.MethodsA retrospective study was conducted on 608 women who tested positive for HPV-DNA during their initial visit to the outpatient department of Shenzhen Longgang Central Hospital from 2018 to 2023 and who had subsequent HPV-DNA testing as part of their post-visit monitoring. The monitoring intervals were every 6 months. The rank sum test was used to analyze ranked data. The Kaplan–Meier method was used to analyze the turning negative time. Univariate analysis was performed using the log-rank test, and multivariate analysis was performed using the Cox model to analyze independent risk factors.ResultsThe results showed that the median age was 40.00 years (interquartile 33.00–47.00 years), the total conversion rate of the HPV-negative patients was 38.98%, and the median conversion time of the HPV-negative patients was 8.95 months (interquartile 4.20–16.175 months). Age, infection status and type of health insurance were significantly correlated with HPV outcome (p < 0.05).ConclusionAmong women infected with HPV, the overall rate of negative HPV infection was 38.93%, and the duration of negative conversion was 8.95 months. The study revealed that age, HPV infection status, and type of medical insurance are independent predictors of the persistence of negative HPV test outcomes.